Pengembangan Sumber Daya Manusia Jabatan Fungsional Analis Kepegawaian di Badan Penelitian dan Pengembangan - Suryana, Nunuk Arie; Agustina , Zulfa Auliyati (Jurnal Ilmu Administrasi Negara (JUAN), 2019)
Human resource planning is done to anticipate the demands or needs of the organization’s workforce in the future, so that a person’s performance in the organization is one of the factors that determine the success of an organization. Human resources that lack attention will lead to unrest, a decrease in enthusiasm and enthusiasm for work, a decline in loyalty and achievement in question. With the decline in enthusiasm and enthusiasm for work, it will result in a high level of absenteeism that can harm the organization. The functional position of the staff analyst is the spearhead of PNS management so that it must understand staffing management starting from recruitment, placement and promotion to dismissal, besides expecting Diklat participants to become agents of change towards the negative image of civil servants and also having to carry out the function of socializing regulatory staff in their work environment . The approach in this study is qualitative. A qualitative approach is used because the main purpose of this study seeks to provide an overview in the implementation of Human Resource Development in the Job Analyst Functional Position in the Health Research and Development Agency. In this study using three components that influence the success of human resource development functional positions of staff analysts, namely individual development, career development, performance management.